Relationship between dental age, chronological age and cervical vertebral maturation in children and adolescents from Bucaramanga, Colombia - Angélica Torres; Angelica Rojas; Ethman A. Torres; Sandra J. Rueda; Martha J. Rodríguez (Universidad de Concepción., 2018)
Objective: To determine the relationship between chronological age and dental age using Demirjian's method and Baccetti's method of cervical vertebral maturation in radiographs of children and adolescents aged 5 to 16 years in the city of Bucaramanga, Colombia. Methods: An analytical observational cross-sectional study was performed in 1385 cephalometric and panoramic radiographs of 775 females and 610 males. Sex, dental age according to the Demirjian's method, chronological age and degree of maturation of the cervical vertebrae according to Baccetti's method were analyzed. The univariate analysis included the calculation of measures of central tendency for quantitative variables, and frequencies and proportions for qualitative variables. Spearman correlation coefficients were calculated in the bivariate analysis. In the multivariate analysis a multiple linear regression was performed. A value of p<0.05 was considered statistically significant. Results: The mean chronological age was 10.8±3.3 years [Median: 11; 95% CI:10.6-10.6]. There was no statistically significant difference according to sex (p=0.3409). The mean of the differences between dental age and chronological age was 0.60±1.44 years. There was a strong and positive correlation between dental age and chronological age with each stage of maturation. Females reached skeletal maturity at an earlier age. Conclusions: Chronological age shows a direct and positive relationship with dental age and stages of skeletal maturation in a Colombian population.